2019
DOI: 10.1093/hmg/ddz071
|View full text |Cite
|
Sign up to set email alerts
|

Robinow syndrome skeletal phenotypes caused by the WNT5AC83S variant are due to dominant interference with chondrogenesis

Abstract: Heterozygous missense mutations in several genes in the WNT5A signaling pathway cause autosomal dominant Robinow syndrome 1 (DRS1). Our objective was to clarify the functional impact of a missense mutation in WNT5A on the skeleton, one of the main affected tissues in RS. We delivered avian replication competent retroviruses (RCAS) containing human wild-type WNT5A (wtWNT5A), WNT5AC83S variant or GFP/AlkPO4 control genes to the chicken embryo limb. Strikingly, WNT5AC83S consistently caused a delay in ossificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…In this study, misexpression of wt or variant hFZD2 in embryonic face did not cause morphological defects in the upper beak but inhibited patterning and ossification. These decreased ossification phenotypes are comparable to the effect of misexpression of ADRS hWNT5A 248G>C variant that caused short and wide limbs and delay in ossification (Gignac et al, 2019). Likewise, in mouse model, an inducible transgene containing Wnt5a inhibited cranial bone formation (van Amerongen et al, 2012).…”
Section: Effects Of Fzd2 Variants On Skeletogenesismentioning
confidence: 72%
See 3 more Smart Citations
“…In this study, misexpression of wt or variant hFZD2 in embryonic face did not cause morphological defects in the upper beak but inhibited patterning and ossification. These decreased ossification phenotypes are comparable to the effect of misexpression of ADRS hWNT5A 248G>C variant that caused short and wide limbs and delay in ossification (Gignac et al, 2019). Likewise, in mouse model, an inducible transgene containing Wnt5a inhibited cranial bone formation (van Amerongen et al, 2012).…”
Section: Effects Of Fzd2 Variants On Skeletogenesismentioning
confidence: 72%
“…This design suitable for studying autosomal dominant mutations that are thought to cause an interference between mutant and wild-type protein. Indeed, our previous work on an autosomal dominant DVL1 frameshift mutations (Gignac et al, 2023) and WNT5A missense mutations (Gignac et al 2019;Hosseini-Farahabadi et al 2017) found evidence for dominant interference that reduced bone size and changed bone shape. FZD2 is ubiquitously expressed in the face in chicken and mouse (Saal et al, 2015;Yu et al, 2012;Yu et al, 2010;Geetha-Loganathan et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The JNK signal results in cytoskeletal changes that affect cell shape, orientation, polarity and directed cell migration ( Butler and Wallingford, 2017 ). WNT5A protein induces JNK-PCP signaling activity as shown in facial and limb mesenchyme ( Geetha-Loganathan et al, 2014 ; Gignac et al, 2019 ; Hosseini-Farahabadi et al, 2013 , 2017 ). WNT5A is expressed in a horizontal band across the frontonasal mass at the stages we imaged here ( Geetha-Loganathan et al, 2009 ) ( Fig.…”
Section: Discussionmentioning
confidence: 99%